2014
DOI: 10.1007/s10238-014-0280-y
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-218 increase the sensitivity of gastrointestinal stromal tumor to imatinib through PI3K/AKT pathway

Abstract: To detect the expressions of microRNA-218 (miR-218) in an imatinib mesylate-sensitive human gastrointestinal stromal tumor (GIST) cells (GIST882) and an imatinib mesylate-resistant cell line (GIST430) and explore the roles of miR-218 and GIST cells in the sensitivity of gastrointestinal stromal tumor to imatinib mesylate and its potential signaling pathways, with an attempt to provide new insights for the treatment of GIST. The GIST cell lines (GIST882 and GIST430) were cultured in vitro. Quantitative real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 30 publications
2
23
0
1
Order By: Relevance
“…These findings confirm that the PI3K/Akt pathway is essential for the development of colon cancer and is a promising target for the treatment of colon cancer. It has been previously reported that the upregulation of miR-218 inhibits the proliferation of oral squamous carcinoma cells by targeting Akt and mTOR (31), and increases the sensitivity of gastrointestinal stromal tumor cells to imatinib through the PI3K/Akt pathway (32). In the present study, we also revealed that the PI3K/Akt signaling pathway may be a potential target of miR-218 using gene target prediction programs.…”
Section: Introductionsupporting
confidence: 60%
“…These findings confirm that the PI3K/Akt pathway is essential for the development of colon cancer and is a promising target for the treatment of colon cancer. It has been previously reported that the upregulation of miR-218 inhibits the proliferation of oral squamous carcinoma cells by targeting Akt and mTOR (31), and increases the sensitivity of gastrointestinal stromal tumor cells to imatinib through the PI3K/Akt pathway (32). In the present study, we also revealed that the PI3K/Akt signaling pathway may be a potential target of miR-218 using gene target prediction programs.…”
Section: Introductionsupporting
confidence: 60%
“…Explorations of the relationship between miRNAs and tumour chemo-sensitivity, in particular, have recently become a research hotspot. Previous studies have confirmed that miR-218 serves as a tumour suppressor in numerous human cancers and over-expressed miR-218 could inhibit the growth and regulate chemo-sensitivity in certain tumours, including gastric cancer and cervical cancer [25, 26]. It is well known that one miRNA may target many genes in different cell systems and miR-218 is no exception.…”
Section: Discussionmentioning
confidence: 96%
“…Reduced or absent expression of the phosphatase and tensin homolog (PTEN) was significantly associated with IM treatment in GIST patient samples, and PTEN deficiency in vitro results in hyperactivation of AKT (9). Two recent studies in IM-sensitive and resistant GIST cellular models established links between KIT activity (modified by specific KIT-targeting miRNAs), AKT expression and phosphorylation, and cell viability and apoptosis (42,43). Hence, AKT stands out as an attractive target for combination therapy with IM.…”
Section: Discussionmentioning
confidence: 99%